Analysis of Systemic Immune-Inflammation Index (Sii) And Cd4 Count In Hiv/Aids Patients With And Without Tuberculosis Co-Infection - Riza Fathiyah; Kartika Paramita; Irda Handayani (CV. Inara, 2025)
Background: The Global Incidence Of Human Immunodeficiency Virus (Hiv) Infection Continues To Rise, With Increased Mortality Observed In The Presence Of Opportunistic Infections Such As Tuberculosis (Tb), Torch Infections (Toxoplasmosis, Rubella, Cytomegalovirus, Herpes Simplex), And Candidiasis. The Systemic Immune-Inflammation Index (Sii), Derived From Neutrophil, Lymphocyte, And Platelet Counts Obtained Through Routine Complete Blood Count Testing, Has Recently Been Explored As A Potential Marker Of Immune Response And Inflammation In Hiv Patients, Particularly In Those With Tb Co-Infection. Objectives: To Analyze The Sii Index And Cd4 Count In Hiv Patients With And Without Tb Co-Infection. Methods: This Retrospective Study Analyzed Secondary Data From Hiv-Infected Patients Treated At Wahidin Sudirohusodo Hospital, Makassar, Between January 2022 And June 2024. The Mann–Whitney U Test Was Used To Compare Sii And Cd4 Counts Between Groups, And Receiver Operating Characteristic (Roc) Curve Analysis Was Performed To Assess The Predictive Value Of Sii For Tb Co-Infection. Results: Among 144 Patients, Sii Values Were Significantly Higher In The Hiv-Tb Co-Infection Group Compared To The Non-Tb Group (P = 0.001). Roc Analysis Revealed That An Sii Cut-Off Value Of 562.3 Yielded A Sensitivity Of 82.4% And A Specificity Of 35.5%, With An Area Under The Curve (Auc) Of 0.661, Indicating Weak Discriminatory Power. Cd4+ T Cell Counts Were Significantly Lower In Patients With Tb Co-Infection (P < 0.001). Conclusion: Sii Was Significantly Elevated In Hiv Patients With Tb Co-Infection, Demonstrating Relatively High Sensitivity And Suggesting Its Potential Utility As A Screening Tool For Identifying Tb Co-Infection In Hiv-Infected Individuals. Cd4+ T Cell Counts Were Also Significantly Lower In The Co-Infection Group, Consistent With Greater Immunosuppression.